2011
DOI: 10.1517/14712598.2011.605353
|View full text |Cite
|
Sign up to set email alerts
|

The immunological era in melanoma treatment: new challenges for heat shock protein-based vaccine in the advanced disease

Abstract: Further investigations are needed to understand the biological basis of immune functions in order to improve the clinical outcome of HSP-based cancer therapy. In the near future, the combination of HSP-based vaccines with other biological compounds might represent a successful strategy in the therapy of advanced melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…In fact, autologous tumor‐derived HSPs (e.g. HSP96‐peptide complex [HSPPC‐96], HSPPC‐70, etc) have been evaluated as tumor vaccines in a variety of phase I‐III trials over a wide range of cancers, with clinical benefit in some melanoma patients …”
Section: Alarmins and Tumor Immunitymentioning
confidence: 99%
“…In fact, autologous tumor‐derived HSPs (e.g. HSP96‐peptide complex [HSPPC‐96], HSPPC‐70, etc) have been evaluated as tumor vaccines in a variety of phase I‐III trials over a wide range of cancers, with clinical benefit in some melanoma patients …”
Section: Alarmins and Tumor Immunitymentioning
confidence: 99%
“…GRP94 plays an important role in immune responses by facilitating MHC class I molecule mediated antigen presentation, and by inducing the maturation and activation of various cells involved in innate and adapted immune responses, including macrophages, DCs, T cells and B cells 109111 . Therefore, it might be expected that GRP94 could elicit an antitumor response.…”
Section: The Role Of Grp94 and Other Chaperones In Antitumor Vaccinationmentioning
confidence: 99%
“…However, no studies have been reported on the potential of 14-3-3γ as a marker for the prognosis of patients with NPC. Clinically, a proteomics study to identify hepatocellular carcinoma (HCC)-related biomarkers found that 14-3-3γ is up-regulated in HCC [36]. Recently, it is reported that 14-3-3γ is a predictor of a high risk of extrahepatic metastases and worse survival in human hepatocellular carcinoma [37].…”
Section: Discussionmentioning
confidence: 99%